Models for Integration of Psychological and Linguistic Knowledge in Complex Forensic Examinations - T. N. Sekerazh (Теория и практика судебной экспертизы)
The article presents complex forensic psychological and linguistic examination models developed basing on various kinds of integration of psychological and linguistic knowledge in solving typical expert tasks. Based on forensic expertise, expert practice, methodological developments in complex, as well as psychological and psychiatric examinations, the author describes the following types of studies: a sequential complex of examinations, parallel complex examination, complex sequential analysis, sequential-parallel complex study.The author also illustrates the sequence of the use and integration of the results of applying specialized knowledge with particular examples.